A novel turbine ventilator with a damper regulator to adjust exhausted air for energy-saving in buildings. (June 2021) - Wang, Bohong; Klemeš, Jiří Jaromír; Malášek, Jiří; Hemzal, Milan; Liang, Yongtu; Zeng, Min
Abstract: Turbine ventilators are widely used for improving indoor air quality. However, the air exhaust flow rate of presently used turbine ventilators increases with wind speed, which results in a much higher air exchange rate than the required air exchange rate for air quality in the winter for heated buildings. A novel turbine ventilator with damper is developed in this paper for the energy saving of buildings under this circumstance. It could stabilise the air exchange rate in buildings to meet the minimum air quality requirement. Experiment and real site studies are conducted to test the performance of the novel device. The experiment verifies that the novel device could reduce unnecessary air exhaust flow rate when the wind speed is high compared with other presently used turbine ventilators. In a day when the wind speed is 8 m/s, the novel ventilator can reduce about 120 m 3 /h air volume flow compared with the presently used ventilator in both kitchen and toilet. The real site measurements show that in the conditions of city Brno-Bystrc, Czech Republic, the novel device can save about 30 EUR/y for one apartment on heating, and 2, 160 EUR/y for a typical panel house (block of flats) which has three entrances, 72 apartments. Highlights: A novel turbine ventilator is developed for energy-saving in buildings. The damper can automatically control the air exhaust flow rate. Experiment and real site studies verify the effectiveness. 120 m 3 /h air volume flow can be reduced when wind speed is 8 m/s. 2160 EUR/y can be saved for a typical block of flats which has 72 apartments.